Rest masses of elementary particles as basic information of Gibbs–Falkian thermodynamics - Straub, Dieter; Balogh, Vilmos (International journal of thermal sciences, 2000)
As developed by G. Falk (following J.W. Gibbs), methods of modern thermodynamics allow by means of the Einstein mechanics to describe as well energy–momentum transports (EMT) which occur under vacuum conditions. Such EMT relations are proved to manifest a set of elementary particles which in its entirety determines real state changes of fluids on the macro-level. EMT differ from each other by their masses at rest ( m # ) resulting as integration constant each. In order to identify m # , Seelig has established a new theory whose physical background is de Broglie's mechanics of matter waves. Seelig's results stand out without exception by their excellent agreement with a lot of measured m # values of elementary particles. Strikingly, the structure of the Seelig equation even permits for an extension upon particles hitherto outside Seelig's approach. This new semi-empirical mass formula agrees with the experimental m # values of all known stabile elementary particles better than 0.085 % on weighted average. The formula has some outstanding properties leading to some remarkable conclusions on Higgs particles and allowing predictions of particles hitherto unknown. Thus, a new key to a uniform understanding of real processes in physics, e.g., in thermal sciences, is now at hand: matter is realized on the micro-level by a finite number of particle classes which are subject to well-posed constraints holding on macro-level for the physical system in question.